POTENSI AKAR BURDOCK SEBAGAI BENTUK PROTEKTIF RADIKAL BEBAS PADA SALURAN PERNAPASAN PEROKOK AKTIF STUDY IN-VIVO PADA TIKUS JANTAN - Imam Agus Faizal; Frinsisca Octaviany; Ira Pangesti; Dini Puspodewi; Arina Lis Sa'adah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Exposure to cigarette smoke is known to trigger oxidative stress and trigger an inflammatory response in lung tissue. Lung organs are highly susceptible to damage due to continuous exposure to pollutants, especially free radicals. This condition has the potential to cause pathological changes in the structure of lung cells. This study aimed to evaluate the difference in histological changes in rat lungs between the group not exposed to conventional cigarette smoke (control group) and the group exposed to cigarette smoke accompanied by the administration of burdock root extract, ethanol solvent, methanol, and vitamin E. Exposure was carried out 7 times for 14 days, using one cigarette for each treatment session. The results of the observation showed that all the groups that received exposure had lung tissue damage. Based on the average histopathological score, the rate of lung damage was grouped as follows: K1 (negative control) of 4.6; K2 (positive control) of 7; P1 (treatment with ethanol) of 5.6; P2 (treatment with methanol) of 8.6; and P3 (treatment with vitamin E) by 6.6. The group with the highest level of damage was P2 (methanol) which fell into the severe damage category, while the lowest level of damage was found in P1 (ethanol), which fell into the light category.